Destabilized 3’UTR elements therapeutically degrade ERBB2 mRNA in drug-resistant ERBB2+ cancer models - Awah, Chidiebere U.; Glemaud, Yana; Levine, Fayola; Yang, Kiseok; Ansary, Afrin; Dong, Fu; Ash, Leonard; Zhang, Junfei; Ogunwobi, Olorunseun O. (Frontiers in Genetics, 2023)
Breast, lung, and colorectal cancer resistance to molecular targeted therapy is a major challenge that unfavorably impacts clinical outcomes leading to hundreds of thousands of deaths annually. In ERBB2+ cancers regardless of the tissue of origin, many ERBB2+ cancers are resistant to ERBB2-targeted therapy. We discovered that ERBB2+ cancer cells are enriched with poly U sequences on their 3’UTR which are mRNA-stabilizing sequences. We developed a novel technology, in which we engineered these ERBB2 mRNA-stabilizing sequences to unstable forms that successfully overwrote and outcompeted the endogenous ERBB2 mRNA-encoded message and degraded ERBB2 transcripts which led to the loss of the protein across multiple cancer cell types both in the wildtype and drug-resistance settings in vitro and in vivo, offering a unique safe novel modality to control ERBB2 mRNA and other pervasive oncogenic signals where current targeted therapies fail.